Proceedings of the Twenty-Eighth International Joint Conference on Artificial Intelligence 2019
DOI: 10.24963/ijcai.2019/29
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Social Influence to Control Elections Based on Scoring Rules

Abstract: Online social networks are used to diffuse opinions and ideas among users, enabling a faster communication and a wider audience. The way in which opinions are conditioned by social interactions is usually called social influence. Social influence is extensively used during political campaigns to advertise and support candidates.Herein we consider the problem of exploiting social influence in a network of voters in order to change their opinion about a target candidate with the aim of increasing his chance to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Wilder and Vorobeychik used the Margin of Victory (MoV) as an objective function and showed that there exists a greedy algorithm that approximates an optimal solution by a factor 1/3(1 − 1/e) for constructive and 1/2(1−1/e) for the destructive case. The same problem has been extended to LTM and general scoring rules [26] by Corò et al [10,11]. They have shown that the problem can be approximated within the same bound.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilder and Vorobeychik used the Margin of Victory (MoV) as an objective function and showed that there exists a greedy algorithm that approximates an optimal solution by a factor 1/3(1 − 1/e) for constructive and 1/2(1−1/e) for the destructive case. The same problem has been extended to LTM and general scoring rules [26] by Corò et al [10,11]. They have shown that the problem can be approximated within the same bound.…”
Section: Related Workmentioning
confidence: 99%
“…The above rule for updating the preference lists is commonly used in the literature [10,25]. In this model, we consider just one message, which contains some positive/negative information about the target party that will affect all the target candidates.…”
Section: Multi-winner Election Controlmentioning
confidence: 99%
“…The authors provide approximation algorithms for plurality voting when the objective function is the maximization of the margin of victory. These approximation results also hold when other voting rules and/or other diffusion models are adopted, as showed by Corò et al (2019bCorò et al ( , 2019a. While the works mentioned above assume that the manipulator has complete knowledge about the problem, some recent work also deals with uncertainty on the network (Abouei Mehrizi et al, 2020).…”
Section: Related Workmentioning
confidence: 72%
“…The works by Wilder and Vorobeychik (2018) and Corò et al (2019bCorò et al ( , 2019a present some limitations when dealing with elections with more than two candidates. A major limitation is the assumption that all the seeds send the same information, and this information is on a single candidate.…”
Section: Related Workmentioning
confidence: 99%
“…Only recently, the setting with multiple candidates has been investigated. In particular, Wilder and Vorobeychik (2018) study the manipulation of a plurality voting based election when the information spread in the network according to an Independent Cascade model; Corò et al (2019) extend this result to a linear threshold diffusion model and arbitrary scoring rules; and Aboueimehrizi et al (2019) allow a manipulator to have imperfect information on the network. However, all of these works still assume the manipulator only sends messages in favour or against a single candidate.…”
Section: Introductionmentioning
confidence: 99%